Propuesta del producto turístico “Las calles históricas de La Candelaria” en la ciudad de Bogotá-Colombia - Cruz Uscategui, Duván Arturo; Bejarano Martínez, Miguel Ángel (Universidad Antonio Nariño, 2022)
This work seeks to develop a proposal for a tourism product focused on the characteristic names of the streets of the Candelaria district based on the tastes and preferences of visitors to this locality with the help of industrial engineering tools. The me thodology used is a mixed approach. First, a documentary review was carried out with the help of positioning Keywords related to tourism, the tourist products offered on this page were compared and 2 popular tourist attractions in the area were chosen to c apture the attention of potential customers visiting La Candelaria. As a third point, the valuation and selection of the streets where the touristic product would take place was carried out with the help of a valuation matrix of the streets visited in the locality of La Candelaria. Subsequently, the strengths, weaknesses, threats, and opportunities of the area were identified and used to create strategies for the design process of the proposal, a survey of visitors to the area was carried out and finally the proposal of the tourist product called The Historic Streets of La Candelar ia was made, including logo, services and attractions, route of the tour, prices and presentation brochure.